The Existence and the Challenges of Sufi Literature in Indonesia - Siraj, Fuad Mahbub; Arif, Ridwan; M. Syadli,; Amril, (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
The article is aimed at elaborating on the challenges of Sufi literature in Indonesia. This research is library research using a historical approach to obtain data and conducting content analysis. This research shows that Sufi literary treasures are the largest and most important part of the Islamic literature treasury. Sufi poets are not only pioneers in the revival of national literature in their countries, but they are also pioneers of the rise of the Islamic world. Sufis did not write mystical and transcendental works which are individualistic in nature. Their works are also associated with a social life that appeared in political allegory and literary whit history patterns. Sufism has influenced Indonesian literature since the early era of the spread of Islam in the Archipelago, i.e., in the 13th century. The emergence and development of Sufi literature in Indonesia is a direct impact on the swift process of Islamization, in which among the main actors are saints, scholars, teachers, and Sufi scholars. The works of the 16th-18th centuries have their position in the overall history of Islamic intellectuals in Indonesia. There are many important aspects in these works, especially those related to the way of life, the picture of the world (weltanschauung), and the value system of society. Even these Sufi works influence modern Indonesian literature. The existence of Sufi literature in Indonesia in this modern era is being challenged. The technical issues such as difficulty in obtaining theory and material resources, as well as references for Islamic aesthetics, literature, and culture, were often propounded as a reason for the less attention to the study of Sufi literature. In reality, the real reason is not purely technical; it is caused by the domination of Western theory in their minds, especially from the philosophy of neo-positivism also there is an assumption that non-Western theory has never grown the relevant theory of literary and aesthetics.